(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The aim of this study is to investigate the impact of certain covariates on obesity. More importantly, we seek to determine the feedback of obesity on depression, and physical activity as they transition from adolescence to young adulthood. Methods: Using 15 years of nationally representative data from 6560 adolescents (Add health data), we estimate feedback and associations between depression, and activity scale on obesity while we adjusted for gender, age, race/ethnicity, socioeconomic status through a GMM logistic regression model with time-dependent covariates. Results: Activity (p<0.001) and depression (p<0.001) have significant impact on Obesity. In early years, alcohol had no impact (p=0.895 and p=0.476) on obesity but in later years it did (p<0.001). In the early years, television hours had an impact but as they got older, it did not. Conclusion: Our findings suggest that public health researchers can target obesity simultaneously with depression, and activity scale. These findings contribute new insights into the feedback of obesity on depression, and activity. This unique model allows segments of associations to be addressed rather than assuming all associations remain the same over 15 years.